What can i feel? : child's play - Kubler, Jess (child's play Sydney, 2011)
"What Can I Feel?" is a children's book that explores various emotions and feelings through engaging illustrations and relatable scenarios. It helps young readers identify and express their emotions, fostering emotional intelligence and awareness. The book often features characters experiencing different feelings, encouraging children to recognize that it's okay to have a range of emotions and to talk about them. Overall, it aims to promote understanding and acceptance of feelings in a fun and accessible way.